2022
DOI: 10.1186/s13287-022-03016-6
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide protects bone marrow mesenchymal stem cells against glucose and serum deprivation under hypoxia via the NRF2 signaling pathway

Abstract: Background Bone marrow mesenchymal stem cell (BMSCs) therapy is an important cell transplantation strategy in the regenerative medicine field. However, a severely ischemic microenvironment, such as nutrient depletion and hypoxia, causes a lower survival rate of transplanted BMSCs, limiting the application of BMSCs. Therefore, improving BMSCs viability in adverse microenvironments is an important means to improve the effectiveness of BMSCs therapy. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 105 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Our results revealed that PRDX2 transfection could increase the proliferation of ADSCs and protect ADSCs from apoptosis and OS in vitro. A possible reason for this is that PRDX2 is an antioxidant enzyme that protects cells, including ADSCs by removing ROS [ 12 , 13 , 25 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed that PRDX2 transfection could increase the proliferation of ADSCs and protect ADSCs from apoptosis and OS in vitro. A possible reason for this is that PRDX2 is an antioxidant enzyme that protects cells, including ADSCs by removing ROS [ 12 , 13 , 25 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs were extracted from epididymal tissue of 4-week-old Sprague-Dawley (SD) male rats [ 24 ]. The cells were cultured in complete medium consisting of low-glucose Dulbecco's modified Eagle's medium (DMEM) (Gibco, USA), 10% fetal bovine serum (FBS) (Gibco, USA), and 1% penicillin-streptomycin solution (containing 100 U/mL penicillin and 100 μ g/mL streptomycin) at 37°C with 5% CO 2 .Then, the ADSCs at passage 3 were collected and incubated with antibodies against CD11b, CD29, CD34, CD44, CD45, and CD90 (all from eBioscience, USA) and detected by flow cytometry (BD FACS Canto, USA) [ 25 ]. As a previous study mentioned [ 24 ], the success of osteogenic and adipogenic differentiation demonstrated the pluripotency of ADSCs (Cyagen, China).…”
Section: Methodsmentioning
confidence: 99%
“…The relative amount of target gene mRNA was normalized to that of GAPDH mRNA in the same sample. The primers' sequences used in cell experiments were designed through PrimerBank (https://pga.mgh.harvard.edu/primerbank/) and the primers' sequences of PKM2 and LDHA were designed through a reference 63 . The sequence of qPCR primers in the rat experiments were listed using r-ACTB and etc.…”
Section: Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…However, although hucMSCs have achieved good efficacy in clinical trials, we still face great challenges. Differences in oxygen concentration and nutritional conditions between in vivo and in vitro may subject hucMSCs to high oxidative stress after transplantation in vivo, reducing colonization and survival rates and preventing effective treatment of damaged sites [ 35 , 7 , 8 ]. Therefore, it is particularly important to explore the molecular mechanisms that cause oxidative stress in hucMSCs, find intervening targets, and genetically modify MSCs to improve therapeutic efficacy in pediatric diseases.…”
Section: Introductionmentioning
confidence: 99%